Dietary whey protein lessens several risk factors for metabolic diseases: a review - Sousa, Gabriela T. D.; Lira, Fabio S.; Rosa, Jose C.; de Oliveira, Erick P. [UNESP]; Oyama, Lila M.; Santos, Ronaldo V.; Pimentel, Gustavo D. (Biomed Central Ltd., 2012)
Obesity and type 2 diabetes mellitus (DM) have grown in prevalence around the world, and recently, related diseases have been considered epidemic. Given the high cost of treatment of obesity/DM-associated diseases, strategies such as dietary manipulation have been widely studied; among them, the whey protein diet has reached popularity because it has been suggested as a strategy for the prevention and treatment of obesity and DM in both humans and animals. Among its main actions, the following activities stand out: reduction of serum glucose in healthy individuals, impaired glucose tolerance in DM and obese patients; reduction in body weight; maintenance of muscle mass; increases in the release of anorectic hormones such as cholecystokinin, leptin, and glucagon like-peptide 1 (GLP-1); and a decrease in the orexigenic hormone ghrelin. Furthermore, studies have shown that whey protein can also lead to reductions in blood pressure, inflammation, and oxidative stress.
Keywords: Whey protein; Obesity; Type 2 diabetes mellitus; Appetite; Inflammation; Hypertension